A case of shiitake dermatitis in the United States. Issue 8 (13th August 2021) - Gomez, Jesus; Sharma, Krishna; Huho, Albert; Gregory, Neal
ABSTRACT: A 65-year-old male presented to our dermatology clinic with a two-day intensely pruritic rash covering his back. The lesions were predominantly on his chest, upper extremity, and back. He denied any prior history of similar rashes and his past medical history was non-contributory. A detailed exposure history revealed the patient had eaten Shiitake mushrooms for dinner 48 hours previously. Physical examination showed a truncal dominant rash. Close-up examination confirmed the papulovesicular nature of the rash with multiple small vesicles grouped both along the breadth and length of each linear streak on an erythematous background. Biopsies showed spongiosis with micro-vesiculation. Blood work showed a nominal CBC and CRP/ESR and serum IgE. The patient was put on topical steroid and the rash resolved in one week. With increasing mushroom consumption [1 ], cognizance of this etiology avoids a diagnostic 'odyssey' and prevents recurrence of this very characteristic rash.